CO2 geological storage in sedimentary basins: An update on the potential and suitability evaluation and a field test - Yujie Diao; Xin Ma; Chenglong Zhang; Xiaolin Jin; Xufeng Li; Chao Zhang (Energy Geoscience)
China has pledged to peak carbon dioxide (CO2) emissions by 2030 and achieve carbon neutrality by 2060. Carbon capture and storage (CCS) will play a key role in these efforts. Over the past several years, the China Geological Survey (CGS) has completed the Suitability Evaluation Map of CO2 Geological Storage in Main Sedimentary Basins in China and Adjacent Sea Regions in 2017. This map reflects the suitability of the first- and secondary-order tectonic units within sedimentary basins for CO2 geological storage for CCS planning. The Junggar Basin is recognized as an important region for future CCS projects. Results from a mesoscale evaluation using the volume method indicate that deep saline aquifers represent the most significant resources for CO2 storage, with potential ranging from 48 × 109 to 164 × 109 t (with a P50 value of 96 × 109 t). The highest storage potential is identified in the central and northern parts of the basin, reaching up to 9.5 × 106 t/km2 at the P50 probability level. In contrast, the hinterland, eastern, and western parts of the basin generally exhibit storage potential of below 1.0 × 106 t/km2 at the same probability level. The CGS has also characterized historical CO2 plume migration in reservoirs at the storage site of the Shenhua CCS demonstration project and conducted numerical simulations of CO2 plume migration for periods of 10 and 20 years following the shutdown of the injection well. The CGS implemented a kiloton-scale pilot test on CO2-enhanced water recovery (CO2-EWR) in eastern Junggar, revealing that CO2 flooding can improve the pressure for fluid production, with the highest ratio of CO2 to produced fluids estimated at approximately 1.2. Besides, an observation field for natural CO2 leakage, covering about 930 m2, was built in Qinghai Province. In natural CO2 fields or at artificial CO2 injection research sites, CO2 leakage points are primarily related to the distribution of faults (especially fault crossing), which can serve as pathways for CO2 leakage. The observation field provides a natural analog to wellbore failure and offers an opportunity to further monitor CO2 geological storage sites. However, it has been inferred that borehole ZK10 at the observation field has become a leakage pathway due to the drilling activities, inadequate well-plugging, and abandonment procedures without considering CO2 corrosion.